Revitalising Waqf Institutions Through a Co-Creation Ecosystem of Public Engagement - Johari, Fuadah; Yusuff, Noraini; Ishak, Nor Syahidah; Misbah, Hanim; Harun, Siti Latipah; Hasbullah, Nurul Adilah; Ahmad Musadik, Siti Hajar Salwa; Ahmad, Azuan (Universal Publishers, 2024)
The current study aimed to evaluate the factors of public willingness to engage in a co-creation ecosystem with waqf institutions in Malaysia. The impacts of trust, reciprocity, commitment, shared social responsibility, loyalty, and satisfaction towards the willingness to co-create in waqf activities among stakeholders in Malaysia were investigated. This approach enhances social innovation to revitalise waqf institutions by fostering greater stakeholder collaboration. Design/methodology/approach: A quantitative research approach was employed by utilising the information-sharing theory. The Statistical Package for Social Sciences (SPSS) software was used to analyse the demographic factor for descriptive analysis along with hypothesis testing using partial least square structural equation modelling (PLS-SEM) and SMART PLS4. The study was conducted between April and August 2023 involving 370 purposively sampled respondents who comprised waqif, Mawquf Alaih, or those with knowledge of waqf endowment. Additionally, the validity of factors influencing waqf stakeholders’ willingness to co-create with waqf institutions in Malaysia was also demonstrated. Findings: Reciprocity, loyalty, and satisfaction positively and significantly influenced the willingness to co-create with waqf institutions, while shared social responsibility and commitment revealed the opposite effect. Research limitations/implications: Given that the current study relied solely on questionnaires for data collection, a qualitative approach (interviews) should be incorporated to provide in-depth data. As the respondents were limited to the general public, data from waqf institutions should also be collected to gain a more comprehensive perspective and generate new ideas to increase a person’s willingness to co-create initiatives in waqf. Practical implications: Significant contributions include encouraging policymakers to develop stakeholder-oriented strategies to promote trust, reciprocity, loyalty, and satisfaction and increase the willingness of waqf stakeholders to share information. Furthermore, the current study highlighted the need for waqf institutions to improve the waqf shared social responsibility and commitment to social innovation with values. Several empirical insights were also outlined, such as bridging the gap between theory and practice in building collegiality and togetherness to enhance waqf contribution among stakeholders. Originality/value: To the best of our knowledge, the present study is among the first to examine public willingness to co-create with waqf institutions. Thus, these findings critically contribute to waqf institutions to strategising and improving waqf sustainability. Specifically of the waqf stakeholders sharing information for co-creation in Malaysia (WSIC-MY)